Phase II LEAP-004 Study of Lenvatinib Plus Pembrolizumab for Melanoma With Confirmed Progression on a Programmed Cell Death Protein-1 or Programmed Death Ligand 1 Inhibitor Given as Monotherapy or in Combination. Issue 1 (1st January 2023) - Arance, Ana; de la Cruz-Merino, Luis; Petrella, Teresa M.; Jamal, Rahima; Ny, Lars; Carneiro, Ana; Berrocal, Alfonso; Márquez-Rodas, Ivan; Spreafico, Anna; Atkinson, Victoria; Costa Svedman, Fernanda; Mant, Andrew; et al.
Abstract : PURPOSE: Effective treatments are needed for melanoma that progresses on inhibitors of programmed cell death protein-1 (PD-1) or its ligand (PD-L1). We conducted the phase II LEAP-004 study to evaluate the combination of the multikinase inhibitor lenvatinib and the PD-1 inhibitor pembrolizumab in this population (ClinicalTrials.gov identifier: NCT03776136 ). METHODS: Eligible patients with unresectable stage III-IV melanoma with confirmed progressive disease (PD) within 12 weeks of the last dose of a PD-1/L1 inhibitor given alone or with other therapies, including cytotoxic T-cell lymphocyte–associated antigen 4 (CTLA-4) inhibitors, received lenvatinib 20 mg orally once daily plus ≤ 35 doses of pembrolizumab 200 mg intravenously once every 3 weeks until PD or unacceptable toxicity. The primary end point was objective response rate (ORR) per RECIST, version 1.1, by independent central review. RESULTS: A total of 103 patients were enrolled and treated. The median study follow-up was 15.3 months. ORR in the total population was 21.4% (95% CI, 13.9 to 30.5), with three (2.9%) complete responses and 19 (18.4%) partial responses. The median duration of response was 8.3 months (range, 3.2-15.9+). ORR was 33.3% in the 30 patients with PD on prior anti–PD-1 plus anti–CTLA-4 therapy. The median progression-free survival and overall survival in the total population were 4.2 months (95% CI, 3.8 to 7.1) and 14.0 months (95% CI, 10.8 to not reached), respectively. Grade 3-5 treatment-related adverse events occurred in 47 (45.6%) patients, most commonly hypertension (21.4%); one patient died from a treatment-related event (decreased platelet count). CONCLUSION: Lenvatinib plus pembrolizumab provides clinically meaningful, durable responses in patients with advanced melanoma with confirmed PD on prior PD-1/L1 inhibitor-based therapy, including those with PD on anti–PD-1 plus anti–CTLA-4 therapy. The safety profile was as expected. These data support lenvatinib plus pembrolizumab as a potential regimen for this population of high unmet need.